Sea-ice meiofauna biodiversity from the Nansen Legacy joint cruise JC2-1 (cruise number: 2021708) ... - Marquardt, Miriam; Pitusi, Vanessa; Bluhm, Bodil; Gradinger, Rolf (The Nansen Legacy Project, 2023)
The data was collected during the Nansen Legacy joint cruise (JC2-1, cruise number: 2021708) from 12.07 - 29.07.2021 onboard the research vessel RV Kronprins Haakon, along a transect in the northern Barents Sea from 76N to 82N. The dataset contains abundance and biomass of sea-ice meiofauna (> 20 µm) including large protists such as foraminifers and ciliates and metazoans eggs. Sea-ice meiofauna were identified and counted with stereo microscopy and result are given as Individuals per liter (cells/L) and Individuals per square meter (Ind/m2). Biomass (μg C Ind.-1) was only determined for alive individuals according to carbon contents for ice meiofauna taxa based on literature summarized in Ehrlich et al. (2021, doi: https://doi.org/10.1525/elementa.2020.00169), and carbon values for foraminifers were provided by de Freitas et al. (2021) for benthic species (Bolivinia sp.: 0.00875 μg C Ind.-1; Elphidium sp.: 0.126 μg C Ind.-1, https://doi.org/10.2113/gsjfr.51.4.249) and Anglada-Ortiz et al. (submitted to ...